Projective varieties with unexpected properties : a volume in memory of Giuseppe Veronese : proceedings of the international conference "Varieties with Unexpected Properties," Siena, Italy, June 8-13, 2004 - Veronese, Giuseppe, 1854-1917; Ciliberto, C. (Ciro), 1950- (Walter de Gruyter, 2005)
Contains refereed papers related to the lectures and talks given at a conference held in Siena (Italy) in June 2004. Some of these papers contain expository sections, which describe the subject of special projective varieties and their applications. This book focusses on the topic of secant varieties and the classification of defective varieties.